DESIGN AND SIMULATION OF OPTIMAL CONTROL SYSTEM WITH ANTI-WINDUP COMPENSATOR FOR UNMANNED HELICOPTER VEHICLE - AGUSTIAN (NIM: 23207032); Pembimbing : Dr. Ir. Arief. Syaichu Rohman, M.Eng.Sc., ERIC
Aerial vehicle is a rather new technology in human technology history which started by Wright Brother success when they flying their first airplane around one hundred years ago. From there, aeronautic technology were expanding rapidly and now unmanned aerial vehicle(UAV) become one subject of technology that more concerned. ItÃ‚Â’s because unmanned aerial vehicle bring opportunity to reducing risk and cost when aerial vehicle on a mission at difficult terrain or at dangerous condition. One kind of aerial vehicle is rotary wing type or helicopter, helicopter has more complicated characteristic dynamic than airplane which brought unique challenge. Dynamic of helicopter actuator practically limited by saturation value, this problem could cause an inconsistency between the plant input and the plant state which known by wind up phenomenon. This phenomenon may cause system performance degradation. This thesis is a research report about the design of optimal control system and antiwindup compensator to overcome directionality problem in case of linear multivariable model of helicopter. The anti-windup design is done by three step design procedure, first step is to design optimal controller, second step is to design optimal full state observer, and the third step is to design static anti-windup compensator to overcome directionality problem. Design of static anti-windup compensator is done by solving some linear matrix inequalities. Simulation of designed optimal control system show good system performance, meanwhile simulation of designed anti-windup sistem show that static compensator have succeded to improve system performance.